Deep Learning Approach and Its Impact on Elementary Students’ Learning Experience and Critical Thinking: An Experimental Study - Endang Purwaningsih; Lilik Sri Hariani; Onik Farida Ni’matullah (Didaktika: Jurnal Kependidikan, 2026)
This study examines the effect of deep learning instruction on elementary school students’ learning experience and critical thinking skills, addressing the need for instructional approaches that promote meaningful learning and higher-order thinking. The research employed a quantitative approach using a Quasi-Experimental Nonequivalent Control Group Design involving fifth-grade students at SD Negeri Kedungdalem II, Probolinggo Regency, during the second semester of the 2025/2026 academic year. The sample consisted of 56 students, with 28 students assigned to the experimental group and 28 students to the control group. The experimental group received deep learning instruction implemented through four stages: concept exploration, analysis and meaning-making, deep reflection, and application of concepts in real-life contexts, while the control group experienced conventional instruction. Data were collected using a learning experience questionnaire and a critical thinking skills test, both of which met validity and reliability criteria. The results showed that the experimental group achieved higher mean scores in learning experience (M = 83.45) and critical thinking skills (M = 78.62) compared to the control group (M = 74.18 and M = 69.07, respectively). Independent Samples t-test results indicated statistically significant differences between the two groups (p < 0.05). These findings demonstrate that deep learning instruction is effective in enhancing meaningful learning experiences and students’ critical thinking skills in elementary education.